2022
DOI: 10.3390/ijms231911163
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Potential Mechanism of Quercetin and Kaempferol against Heat Stress-Induced Sertoli Cell Injury: Through Integrating Network Pharmacology and Experimental Validation

Abstract: Quercetin and kaempferol are flavonoids widely present in fruits, vegetables, and medicinal plants. They have attracted much attention due to their antioxidant, anti-inflammatory, anticancer, antibacterial, and neuroprotective properties. As the guarantee cells in direct contact with germ cells, Sertoli cells exert the role of support, nutrition, and protection in spermatogenesis. In the current study, network pharmacology was used to explore the targets and signaling pathways of quercetin and kaempferol in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…The kaempferol exhibited the antioxidant properties to improve the Leydig cells membranes and facilitate cholesterol transfer into mitochondria ( Alam et al , 2020 ), subsequently improving steroidogenesis as StAR protein levels and CYP11A1, 3β-HSD, and 17β-HSD activities and testosterone concentration were upregulated ( Liu et al , 2022 ) as reported in the current research which illustrated that kaempferol administration caused testicular upregulation 3β-HSD, 17β-HSD, and CTP11A1 enzymes and StAR protein gene expression which positively effect on testosterone levels in rats cotreated with kaempferol. Furthermore, the administration of vitamin E following exposure to lead acetate caused elevation of testicular 13β-and 17β- HSD activities and StAR levels due to the ability of vitamin E to promote gene expression of StAR protein and mRNA steroidogenic enzyme in Leydig cells that can upregulate testosterone concentration ( Malmir et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The kaempferol exhibited the antioxidant properties to improve the Leydig cells membranes and facilitate cholesterol transfer into mitochondria ( Alam et al , 2020 ), subsequently improving steroidogenesis as StAR protein levels and CYP11A1, 3β-HSD, and 17β-HSD activities and testosterone concentration were upregulated ( Liu et al , 2022 ) as reported in the current research which illustrated that kaempferol administration caused testicular upregulation 3β-HSD, 17β-HSD, and CTP11A1 enzymes and StAR protein gene expression which positively effect on testosterone levels in rats cotreated with kaempferol. Furthermore, the administration of vitamin E following exposure to lead acetate caused elevation of testicular 13β-and 17β- HSD activities and StAR levels due to the ability of vitamin E to promote gene expression of StAR protein and mRNA steroidogenic enzyme in Leydig cells that can upregulate testosterone concentration ( Malmir et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the effects of kaempferol on the reproductive system have not yet been fully reported. Kaempferol, like other flavonoids that affect LH-and FSH-secreting gonadotroph cells by incrementing their secretory granules ( Zhang et al , 2023 ), which results from the ability of kaempferol to upregulate hypophyseal GnRHr , FSHβ , and LHβ genes due to kaempferol’s antioxidant, antiapoptotic, and anti-inflammatory effects ( Liu et al , 2022 ). In addition, kaempferol has the ability to upregulate the testicular receptor expression of LH and FSH due to its powerful antioxidant properties that protect Leydig and Sertoli cells from Pb oxidative damage ( Lee et al , 2023 ), which promotes testicular steroidogenic enzyme expression which enhanced testosterone biosynthesis, as well as improvement the count, and viability of sperm ( Kluska et al , 2022 , Liu et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations